Reprogramming of Mouse, Rat, Pig, and Human Fibroblasts into iPS Cells - Rajarajan, Kuppusamy (Curr Protoc Mol Biol, 2012)
The induction of pluripotency in somatic cells by transcription factor overexpression has been widely regarded as one of the major breakthroughs in stem cell biology within this decade. The generation of these induced pluripotent stem cells (iPSCs) has enabled investigators to develop in vitro disease models for biological discovery and drug screening, and in the future, patient-specific therapy for tissue or organ regeneration. While new technologies for reprogramming are continually being discovered, the availability of iPSCs from different species is also increasing rapidly. Comparison of iPSCs across species may provide new insights into key aspects of pluripotency and early embryonic development. iPSCs from large animals may enable the generation of genetically-modified large animal models or potentially transplantable donor tissues or organs. In this unit, we describe the procedure for the generation of iPSCs from mouse, rat, pig and human fibroblasts. We focus on lenti- and retroviral infection as the main platform for pluripotent transcription factor overexpression since these reagents are widely-available and remain the most efficient way to generate iPSC colonies. We hope to illustrate the basic process for iPSC generation in these four species in such a way that would enable the lowering of the entry barrier into iPSC biology by new investigators.